Watermarking-based image inpainting using haftoning technique. - Hung, Kuo-Ming (Journal of Applied Science and Engineering)
This study proposes a novel image inpainting technique based on watermarking and halftoning.The LSB method is used to embed error diffusion halftone image into original image for protecting the image. In image repair process, we use LSB method to extract the halftone information, and the reference image is achieved from LUT inverse halftone. Finally, the reference image is used to finish the image inpainting work. Experimental results show the performance of our method is very excellent in image inpainting.